PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN PANAKKUKANG - Aprizal Aprizal (BJRM (Bongaya Journal of Research in Management), 2019)
Based on factors that affect the performance of employees at the panakkukangsub-district office, the city of Makassar can be said to be not optimal. Where, seen fromseveral symptoms, among others, lack of enthusiasm in work, they are more concernedwith discuccions outside of work than looking for or completing the work itself, there arestill some employees who come or enter the office not on time as well as leave the officenot according to the prevailing working hours. Then an inadequate work environment sothat employee performance declines.The purpose of this study was to dtermine the effectof motivation and work environment simultaneously on employee performance at the macassar city sub-district panakkukang office. With a sample of 53 responden from 53populations. By using multiple linear regression analysis. The results of study show thatthe motivation variable has a positive and significant effect on employee performancewith a significant value 0.002 and the work environment variable with a value of 0.002.Adjusted coefficient of determination of ,451 or 45,1%. This means that employee performance can be explained by motivation and work environment while the remaining7.9% the possibility can be explained by other factors outside of the model included inthis study, for example, work stress, work discipline, and leadership.